High speed radiation tolerant optical links based on coarse wavelength division multiplexing. (28th February 2023) - Marcon, L.; Scarcella, C.; Detraz, S.; Lalović, M.; Olantera, L.; Prousalidi, T.; Sandven, U.; Sigaud, C.; Soós, C.; Troska, J.
Abstract: The upgrade of CERN's accelerator complex requires improved beam instrumentation systems that will generate an increased volume of data to be transferred from the radiation areas to the back-end. A solution that increases the throughput of already deployed fibers, with minimal increase of the system complexity, consists in implementing the coarse wavelength division multiplexing (CWDM) technique where independent optical carriers at properly spaced wavelengths are multiplexed into a single fiber. In this paper we describe the CWDM Link project, whose scope is to design and build a high-speed radiation-tolerant optical link based on four CWDM channels. We will also provide details of commercially-available CWDM components and their radiation resistance.